2016
DOI: 10.17161/jomr.v2i2.5848
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Economic Diversity in U.S. Public Montessori Schools

Abstract: As public Montessori schools rapidly expand through the United States, the question then arises: What population of students do the schools serve? This study presents a new empirical data set examining the racial and economic diversity of 300 whole-school, public Montessori programs open in 2012–2013, where the entire school uses the Montessori Method. While school-choice scholars are concerned that choice programs like Montessori lead to greater student segregation by race and social class, this study finds a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 28 publications
(16 reference statements)
2
41
0
Order By: Relevance
“…17 However, random assignment of children to Montessori versus non-Montessori schools for the purposes of a randomised control trial would be very difficult to achieve because it would take away parental choice.…”
Section: Evaluations Of Montessori Educationmentioning
confidence: 99%
“…17 However, random assignment of children to Montessori versus non-Montessori schools for the purposes of a randomised control trial would be very difficult to achieve because it would take away parental choice.…”
Section: Evaluations Of Montessori Educationmentioning
confidence: 99%
“…Today, in a landscape of increasing school segregation around the United States (Orfield, Kucsera, & Siegel-Hawley, 2012), public Montessori schools remain racially diverse (Debs, 2016b). This racial 3 diversity is important because research has consistently shown that students attending racially diverse schools have higher achievement in mathematics (Berends & Penaloza, 2010;Newton, 2010) and literacy (Benson & Borman, 2010) and build more expansive social networks (Braddock & Gonzalez, 2010;Goldsmith, 2010;Wells, Holme, Revilla, & Atanda, 2009).…”
Section: Public Montessori Education and Racial Diversitymentioning
confidence: 99%
“…Half of the 300 schoolwide, public Montessori programs enroll a racially diverse student body (between 25% and 75% students of color). In 23% of these schools, a majority (75%-100%) of enrolled students are students of color (Debs, 2016b). Half of these 300 schoolwide programs are located in urban areas (Debs, 2016b).…”
Section: Public Montessori Education and Racial Diversitymentioning
confidence: 99%
See 2 more Smart Citations